Development of Camera-Based Rainfall Intensity Measurement Tool with Fourier Transform Analysis - Sirenden, Bernadus Herdi; Manao, Arisman; MN, Nasruddin (Journal of Technomaterial Physics, 2021)
In this research, the development of a camera-based rainfall intensity measuring instrument with the Fourier Transform Analysis has been carried out. The ESP32 CAM Microcontroller was used to capture images and record rainfall videos. The research objective was to design a development model for measuring rainfall intensity, understanding the working principle of the tool, and knowing the histogram of the rainfall intensity video recording produced by the rainfall intensity detection tool. The research consisted of several stages, namely literature study, design of research tools and components, system design, assembly of tools, testing of all components, programs and screen record testing and image capture. The design model for the development of a measuring instrument for rainfall intensity that has been made is that when water flows through the shower there will be rainfall. The process of rainfall will be captured and recorded by the ESP32 CAM Microcontroller which is accessed via a computer device. Experiments were carried out ten times, with a time span of 60 seconds per experiment and an increase in rainfall every minute, then the data was processed using python software in the form of a histogram (grayscale), which would be analyzed using the Fourier Transform Analysis method. The results showed that the development of a camera-based rainfall intensity gauge has worked well.